Gonarthrosis related changes in quadriceps muscle architecture and physical function outcomes in women - Rukiye Çiftçi; Ahmet Kurtoğlu; Özgür Eken; Monira I. Aldhahi (Scientific Reports)
Abstract This study aimed to assess the effects of gonarthrosis on quadriceps muscle architecture and fatigue, physical function, and postural balance in women compared with healthy controls. Eighty-one females diagnosed with gonarthrosis (n = 40) and healthy control group (n = 41) aged between 47 and 77 years participated in the study. After demographic data were collected, right and left rectus femoris (RF), vastus intermedius (VI), vastus lateralis (VL) thicknesses and RF pennation angle (PA) were determined using a 2D real-time ultrasound device (USG). RF and VI depths and RF cross-sectional area (CSA) were obtained using ultrasound with the probe positioned in a transverse orientation to the muscle. In addition, the participants underwent the timed up and go test (TUG), 30-sec sit-and–up test (SU30s), and completed the Fatigue Severity Scale (FSS). The relationship between functional tests and right and left quadriceps muscle architecture parameters was also analyzed. In our study, the right CSA (p < .001, t=− 8.609, ES = 1.92), left VL (p = .020, t= − 2.365, ES = 0.052), and left CSA (p < .001, t=− 10.164, ES = 2.26) were significantly higher in the healthy group. Conversely, TUG (p < .001, t = 4.882, ES = 1.08) and FSS (p < .001, t = 10.362, ES = 2.29) were significantly higher in the gonarthrosis group, while SU30s values were higher in the control group (p < .001, t = − 12.262, ES = 2.73). Additionally, a negative correlation was observed between SU30s and CSA, whereas TUG and FSS showed a positive correlation with CSA (p < .001). According to the results of our study, some morphological losses were observed in the quadriceps muscle architecture of participants with gonarthrosis. Decreases in CSA affect functional performance. Determination of quadriceps muscle architecture in patients with gonarthrosis can be used to predict functional loss.